Autologous stem cell transplantation for HIV-associated lymphoma in the antiretroviral and rituximab era: a retrospective study by the EBMT Lymphoma Working Party - Hübel, Kai; Dreger, Peter (Bone marrow transplantation, 2019)
The present study aimed at describing the outcome of patients with HIV-associated lymphomas following autologous hematopoietic stem cell transplantation (autoHCT) in the rituximab and combined antiretroviral therapy (cART) era. Eligible for this retrospective study were HIV-positive patients with lymphoma who received autoHCT between 2007 and 2013. A total of 118 patients were included with a median age of 45 years (range 24-66). Underlying diagnoses were diffuse large B cell lymphoma in 47%, Hodgkin lymphoma in 24%, Burkitt lymphoma in 18%, and plasmablastic lymphoma in 7% of patients. Disease status at autoHCT was complete remission in 44%, partial remission (PR) in 38%, and less than PR in 18% of the patients. With a median follow-up of 4 years, 3-year non-relapse mortality, incidence of relapse, progression-free survival (PFS) and overall survival (OS) were 10%, 27%, 63% and 66%, respectively. By multivariate analysis, disease status less than PR but not CD4+ cell count at the time of autoHCT was a significant predictor of unfavorable PFS and OS. In conclusion, in the era of cART and chemoimmunotherapy, the outcome of autoHCT for HIV-related lymphoma is driven by lymphoma-dependent risk factors rather than by characteristics of the HIV infection.
Gesehen am 29.10.2019